2018
DOI: 10.3389/fpls.2017.02204
|View full text |Cite
|
Sign up to set email alerts
|

Improving Crop Yield and Nutrient Use Efficiency via Biofertilization—A Global Meta-analysis

Abstract: The application of microbial inoculants (biofertilizers) is a promising technology for future sustainable farming systems in view of rapidly decreasing phosphorus stocks and the need to more efficiently use available nitrogen (N). Various microbial taxa are currently used as biofertilizers, based on their capacity to access nutrients from fertilizers and soil stocks, to fix atmospheric nitrogen, to improve water uptake or to act as biocontrol agents. Despite the existence of a considerable knowledge on effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
157
3
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(185 citation statements)
references
References 60 publications
15
157
3
10
Order By: Relevance
“…Similarly, P-solubilizing bacteria (e.g., Agrobacterium radiobacter, Bacillus megaterium; Shankaraiah, Hunsigi, & Nagaraju, 2000), Acidithiobacillus oxidizing bacteria (Stamford, Lima, Lira, & Santos, 2008), and phosphobacteria (Ramesh, Chinnusamy, & Jayanthi, 2002), and mycorrhizal associations (e.g., Aspergillus awamori; Shankaraiah et al, 2000) have been shown to enhance P availability to sugarcane in P-deficient soils, but their ability to offset crop P fertilizer inputs still needs to be proven (Gopalasundaram, Bhaskaran, & Rakkiyappan, 2012). For example, Schütz et al (2018) showed that microbial P solubilizers and arbuscular mycorrhizal fungi can enhance yield by 15% in tropical soils with low levels of plant available P. Research is needed to identify microbial strains that can tolerate P fertilizer inputs while facilitating soil P mobilization and plant uptake, and to develop more integrated practices that combine crop and microbial engineering with lower and more targeted P fertilizer inputs (Rowe et al, 2016;Withers et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…Similarly, P-solubilizing bacteria (e.g., Agrobacterium radiobacter, Bacillus megaterium; Shankaraiah, Hunsigi, & Nagaraju, 2000), Acidithiobacillus oxidizing bacteria (Stamford, Lima, Lira, & Santos, 2008), and phosphobacteria (Ramesh, Chinnusamy, & Jayanthi, 2002), and mycorrhizal associations (e.g., Aspergillus awamori; Shankaraiah et al, 2000) have been shown to enhance P availability to sugarcane in P-deficient soils, but their ability to offset crop P fertilizer inputs still needs to be proven (Gopalasundaram, Bhaskaran, & Rakkiyappan, 2012). For example, Schütz et al (2018) showed that microbial P solubilizers and arbuscular mycorrhizal fungi can enhance yield by 15% in tropical soils with low levels of plant available P. Research is needed to identify microbial strains that can tolerate P fertilizer inputs while facilitating soil P mobilization and plant uptake, and to develop more integrated practices that combine crop and microbial engineering with lower and more targeted P fertilizer inputs (Rowe et al, 2016;Withers et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…Rhizosphere competence and survival of microbial inoculants can be influenced by interactions with the native soil microbiome and by abiotic stress factors (van Veen et al, 1997;Lugtenberg and Kamilova, 2009). Moreover, in agricultural systems, the amount (Dogra and Dudeja, 1993;Nouri et al, 2014;Huang et al, 2017;Schü tz et al, 2017) and the type of the applied fertilizers can also play an important role. In the latter context, the preferential perform-ance of PGPMs in combination with N-rich organic fertilizers has been repeatedly reported (Abbasi et al, 2015;Thonar et al, 2017;Mpanga et al, 2018;Bradá č ová et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence for selective interactions between the form and the amount of fertilizers and microbial inoculants. In a meta-study covering 171 publications, Schütz et al [11] demonstrated that P-solubilizing microorganisms as plant inoculants were mainly effective in soils with moderate available P levels (25-35 kg P ha −1 ) but not on low P soils or at higher P availability. In an investigation with Bacillus-, Pseudomonas-, and Trichoderma-based inoculants in maize on six different soils in five countries with eight different types of fertilizers based on recycling products from organic and inorganic waste materials, Thonar et al [12] reported superior performance particularly in combination with composted animal manures.…”
Section: Introductionmentioning
confidence: 99%